Repeat victimization among adolescents and young adults - Lauritsen, Janet Lynn (Journal of quantitative criminology, 1995)
Prior research has shown that victimization incidents are disproportionately concentrated among relatively few victims and that prior victimization is a consistent predictor of future risk. This paper expands existing knowledge on victimization by describing temporal patterns of risk and by developing and testing alternative explanatory models of the link between past and future risk. Analyses based on panel data from the National Youth Survey support both state dependence and heterogeneity interpretations of the correlation in risk over time. In other words, prior victimization predicts future risk in part because it alters something about the individual, and because it indicates an unmeasured propensity for victimization that persists over time. The theoretical implications of these findings, including the feasibility of a victim labeling perspective, are discussed.